Evolution of electromechanical and morphological properties of piezoelectric thin films with thermomechanical processing. (5th December 2016) - Xu, Zhe; Baniasadi, Mahmoud; Moreno, Salvador; Cai, Jizhe; Naraghi, Mohammad; Minary-Jolandan, Majid
Abstract: Piezoelectric polymers (PVDF and its co-polymers) in film and nanofiber forms are increasingly used for sensing, actuation and energy harvesting. Given the semi-crystalline structure of these polymers, their electromechanical coupling behavior changes with thermomechanical processing. This article reports on the evolution of the mechanical properties, piezoelectric properties and morphology of P(VDF-TrFE) poly[(vinylidenefluoride)- co -trifluoroethylene] piezoelectric polymer thin films fabricated by spin-coating during thermal annealing and drawing, studied via tensile test, polarized optical microscopy, X-ray diffraction, polarized FTIR, and piezoresponse force microscopy (PFM). The results show that annealing and drawing process result in ∼10 and 13 folds improvement in the elastic modulus and strength of the films, respectively. In addition, the piezoelectric constant and electromechanical coupling improves by 30% and more than 17 times, respectively. These changes are accompanied by 65% increase in the percentage of the crystallinity of the semi-crystalline piezoelectric films, compared to the as-fabricated films. Graphical abstract: Highlights: Investigated the evolution properties of piezoelectric polymer films by annealing and drawing. Processing resulted in ∼10 and 13 folds improvement in the elastic modulus and strength of the films. Piezoelectric constant and electromechanical coupling improved by 30% and more than 17 times.